Meeting the mental health needs of women in Irish prisons: A qualitative multi-stakeholder perspective to inform healthcare practice - Ann-Marie Bright; Agnes Higgins; Annmarie Grealish (PLoS ONE, 2025)
The rate of female incarceration to prison has grown by approximately 60% since the year 2000. Mental ill-health is over-represented in the female carceral population and the experiences of women in the context of prison mental health services are largely invisible in empirical literature. The aim of this study was to highlight the under-represented narratives of women in prison and prison personnel to inform nursing practice and prison mental health service planning and delivery. A qualitative approach was used underpinned by institutional ethnography. Data were collected across two (n = 2) female prisons in the Republic of Ireland. Purposive and snow-ball sampling was used to recruit both women in prison and prison personnel to the study. One-to-one semi-structured interviews were conducted with participants. Reflexive Thematic Analysis was used to analyse the data. Ethical approval was granted by the Irish Prison Service and noted with Education & Health Sciences Research Ethics Committee at the University of Limerick. A total of twenty-five (n = 25) women in prison and twenty (n = 20) prison personnel participated in the study. Four analytic themes were identified from the data and present narratives that centre around women’s knowledge of and access to prison mental health services; women’s relationships with peers and prison officers; women’s relationships with medical doctors and medicine and organisational issues related to the provision of mental health services for women in prison. The barriers to accessing mental health services in the Irish prison context are numerous and complex. The findings from this study demonstrate the importance of approaching care with compassion and understanding and making inclusion health a priority.